Identification Of Novel Genes Involved In Azole Resistance And Sequence Analysis Of Known Resistance Genes In Candida Tropicalis - Low, Lee Yean (2007)

(untitled)
Opportunistic fungal infections resistant to antifungal agents have been increasingly documented in recent years and their fkequency will likely continue to increase. This phenomenon appears due to extensive use of antifungal agents to treat fungal infections especially candidiasis in irnmunocompromised patients. In this project, the molecular alterations in Candida tropicalis azole-resistant strain which may have contributed to the development of resistance against fluconazole have been investigated and potential drug targets have been identified. The differential gene expression profiles of a C-tropicalis resistant clinical strain, a C.fropicalis ATCC 750 induced-resistance strain and a Cadidla h e i inherent resistant strain were compared with a Candida tropicalis ATCC 750 susceptible strain via Differential Display Reverse Transcription Polymerase Chain Reaction. One hundred and six transcripts were found differentially displayed whereby 63 were up-regulated; three were down-regulated aMi 40 were non-expressed in the susceptible strain. Functional study of up-regulated transcripts in the resistant strain revealed that these transcripts were involved in cell wall maintenance (15%), transport function (12949, iii stress response (100/o), cell adherem (lo%)), cell defense (7%), morphogenesis (5%) and other functions (29%), whereby, 12% of the over-expressed transcripts are previously uncharacterized hypothetical protein. From our study, we found that other than ATP-binding cassette transporter, hexose transporter and KpsM (polysialic acid transporter) might play an important role in fluconazole drug efflux in C. tropicalis resistant strain. In developing fluconmole resistance, the C. tropicalis strain, is likely to increase the cell wall integrity and become more virulent by changing its gene regulation. Consistent with previous finding, we also - found that ADHl (alcohol dehydrogenase) was overexpressed in the resistant strain. We suggest that ADHl might be a potential novel drug target. In the sequence analysis of known resistance genes, 5 and 2 point mutations were reported in ERG11 (Lanosterol Demethylase) and CDRI (Candida Drug Resistance 1) of the clinical resistant strain, respectively. The point mutations were T867C, G1552A, T1555C, G1557T and G2016A in ERGII; C251A and A252C in CDRI. However, the contribution of these mutations in the activation of trans-regulatory factors that may thus result in up-regulation of mole-resistant transporter genes is still unknown.